Analisis Gaya Belajar VAK Mahasiswa Pendidikan Guru Sekolah Dasar Universitas Peradaban - Iwan Muzaki; Sulis Susilawati; Anis Dwi Marshella; Eka Trisnawati (S&Co Publishing, 2025)
This study analyzes the VAK (Visual, Auditory, Kinesthetic) learning styles among students of the Primary School Teacher Education Program (PGSD) at FKIP Universitas Peradaban. Using a quantitative survey method, data were collected from 80 PGSD students through a questionnaire comprising of 21 statements and analyzed using descriptive statistics. Results show that the visual learning style is the most dominant (35%), followed by auditory (27.5%) and kinesthetic (16.25%). Additionally, 21.25% of students exhibited mixed learning styles: visual-auditory (7.5%), visual-kinesthetic (7.5%), auditory-kinesthetic (3.75%), and all three styles combined (2.5%). These findings highlight the importance of understanding students’ learning profiles. Visual learners excel in structured planning and visual media use, auditory learners in verbal communication, and kinesthetic learners in activity-based learning. Mixed styles indicate cognitive flexibility and adaptability. The study underscores the need for PGSD programs to implement integrated, multimodal learning strategies—such as infographics, group discussions, interactive seminars, podcasts, simulations, and project-based learning. These approaches enhance learning effectiveness and prepare future teachers to apply differentiated instruction in elementary classrooms, ultimately improving educational quality.